KONTRIBUSI PENDAPATAN WANITA BURUH TANI KELAPA SAWIT TERHADAP PENDAPATAN RUMAH TANGGA DI DESA MALIK KABUPATEN BANGKA SELATAN: Contribution of the Income of Women Oil Palm Farmworkers to Household Income in Malik Village, South Bangka Regency - Ayu, Rahayu; Yulia, Yulia; Muntoro, Muntoro (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
This study aims to calculate the contribution of the income of women oil palm farmworkers to household income and analyze the factors that affect the income of women oil palm farmworkers in Malik Village, South Bangka Regency. The time and place of this research will be carried out in June 2023 on women oil palm farm workers in Malik Village, Payung District, South Bangka Regency. The research method used in this study is a survey method, and the sampling method used in this study is saturated sampling with a sample size of 34 respondents. The data collection methods used are observation, interview, and questionnaire methods. The data analysis method uses revenue contribution and multiple linear regression with SPSS 26.0 software. The results showed that 1) The total income contribution of women oil palm farmworkers received in May was 188.375%, with an average of 55.40% to household income. 2) The factors affecting the income of women oil palm farm workers in Malik Village are working days, number of family members, and wages.